The link between customer profitability in business-to-business markets and the nature of business relationships : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing, Massey University, Wellington campus - Balasubramanian, Ravi (Massey University, 2012)
Empirical studies on customer profitability in business markets have reported wide profitability variation and a skewed distribution, typically a small number of very profitable customers and a much larger number that are marginally profitable or unprofitable. While some studies have attempted to investigate the contribution of financial factors to this pattern, the contribution to customer profitability of non-financial factors, such as the nature of business relationships, has received very little attention. This gap exists despite the wide acceptance amongst practitioners of the importance of business relationship development with customers and of business relationships as a field of academic research. Business relationship development efforts are made with an expectation that they will result in improved financial results, but academic research has not established this based on objective financial measures of customer profitability. To investigate whether a link exists between business relationships and customer profitability, it was hypothesised that multiple facets of the business relationship should be represented and may necessitate adopting constructs from different theoretical frameworks. Thus the proposed theoretical model used behavioural and cognitive constructs based on relationship connectors, environment factors, communication quality, communication quantity, conflict, customer characteristics and commitment. The customer profitability measures were based on traditional financial data but were extended to include imputed costs of other resource usage such as delayed payments, documentation costs and shipment to multiple destinations. Since the research required matching customer profitability measured as a financial outcome with the nature of the business relationship with each customer, data was obtained from a single participating organisation. Relevance of the proposed theoretical constructs to the context of the participating organisation was checked through a qualitative investigation using in-depth interviews with key informants. The subsequent quantitative study used an online survey instrument to obtain data from the organisation’s sales persons on the nature of the relationships with customers. Financial data for computing individual customer’s profitability was obtained from relevant company records. Structural Equation Modelling was used to test and estimate the theorised relationships between constructs. Confirmatory factor analyses revealed the need to make some changes to the original model, but the constructs in the final model demonstrated good discriminant validity. The good fit of the proposed theoretical model to the actual data confirmed the relevance of constructs used in the theoretical model to represent the multifaceted nature of business relationships. The main finding of this research is that commitment to a business relationship with customers is adversely affected by customer profitability factors. An increase of 1 standard deviation in customer profitability variation factors results in a reduction in commitment levels of 0.28 standard deviation units. In this study, customer profitability factors are represented by four indicators: customer profit value, cost of goods, documentation cost and number of destinations. This construct reflects the relative impact of the revenue and cost indicators on individual customer profitability. Commitment plays a central role in linking the constructs representing the nature of business relationships and customer profitability factors. The indicators for commitment assessed expectations of continuity in a relationship and whether expected benefits were realised, and these represent the affective and calculative dimensions of commitment described in the literature. The calculative dimension reflects the expectation of economic returns as a result of commitment to a relationship. Reduction in profits from the customer will adversely affect the calculative dimension and may account for the negative value for the link with customer profitability factors. On the other hand, the affective dimension of commitment reflects the attitudes and beliefs and generalised regard about the relationship and can be linked to efforts to build the business relationship. The nature of the business relationship comprises four constructs; relationship connectors, communication quality, communication quantity and conflict, and represents facets of how a relationship is viewed; this may account for its link with commitment. Environment factors, which include competition and market price fluctuations for the product categories, represent the main set of factors outside the control of the firm and have an impact on revenue as well as commitment to the relationship with customers. The contribution of price changes to revenue and profitability represents an additional element in determining customer profitability. In this study, substantial price increases from products sold to the top decile customers helped offset cost increases and improved the profitability of these customers. From a practitioner’s perspective, the main utility of these findings lies in the importance of integrating customer profitability measures in relationship development efforts. For a more accurate assessment of returns, customer profitability measures should go beyond normal accounting data and include estimates of other resource usage such as documentation costs. Such improved customer profitability measures can help in differentiating customers based on objective outcomes and provide a basis for developing customer portfolios with appropriate relationship development strategies. The differentiation would also imply that commitment to a business relationship has to be contingent on obtaining the expected financial return from the business relationship.
Keywords: Customer profitability; Customer relations; Business relationships